Readiness of Pre-Service Elementary School Teacher to Implement PBL and HOTS in Learning Geometry - Rostika, Deti; Hidayah, Nurul; AM, Muh. Asriadi (Jurnal Pendidikan Progresif, 2023)
Readiness of Pre-Service Elementary School Teacher to Implement PBL and HOTS in Learning Geometry. This survey research aims to assess the comprehension of elementary school teacher education students regarding PBL and HOTS and elucidate the application of PBL and HOTS in elementary geometry education. The study engaged 18 elementary school teacher education students at UPI Cibiru Campus. Findings reveal that these students possess a solid understanding of PBL and a very high level of comprehension of HOTS. The proposed implementations of PBL in geometry education exhibit variations, while others have yet to integrate PBL into their Lesson Implementation Plans. The application of HOTS also varies, with some encompassing all its components, while others fall short. In conclusion, prospective teachers exhibit a robust initial grasp of PBL and HOTS, but a consistent application is essential to foster confidence in practical teaching at elementary schools. Keywords: PBL, HOTS, geometry learning, elementary school.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202339